Perceived Organizational Support On Employee Creativity: The Mediating Role Work Engagement As A Mediator - Widya Nengrum; Andika Baskara; Annisa Fajri (UNIVED Press, 2025)
In this era of global competition, continuous development creates challenges for organizations and demands human resources (HR) to be more creative. Human Resources are valuable assets that need to be considered by companies. This study describes how employee creativity, work engagement, and perceived organizational support (POS) relate to one another in organizations. The degree to which workers feel supported by the company is reflected in POS, and this has been shown to have a big impact on worker engagement and innovation. The association between POS and employee creativity is found to be mediated by work engagement. Data from 123 randomly chosen respondents is analyzed quantitatively in this study using SmartPLS. The analysis's findings show that employee job engagement and creativity are positively impacted by perceived organizational support, with work engagement considerably enhancing this link. This study emphasizes how crucial it is to establish a positive work atmosphere in order to foster employee engagement and innovation.